Formation of ore minerals in metamorphic rocks of the German continental deep drilling site (KTB) - Kontny, Agnes; Friedrich, G.; Behr, H. J.; Wall, Helga de; Horn, E. E.; Möller, P.; Zulauf, G. (Journal of geophysical research. Solid earth, 1997)
The German Continental Deep Drilling Program (KTB) drilled a 9.1 km deep profile through amphibolite facies metamorphic rocks and reached in situ temperatures of 265°C. Each lithologic unit is characterized by typical ore mineral assemblages related to the regional metamorphic conditions. Paragneisses contain pyrrhotite + rutile + ilmenite ± graphite, metabasic units bear ilmenite + rutile + pyrrhotite ± pyrite, and additionally, the so-called variegated units yield pyrrhotite + titanite assemblages. In the latter unit, magnetite + ilmenite + rutile + titanite assemblages related to the lower amphibolite facies breakdown of ilmenite-hematite solid solution also occur locally. Retrograde hydrothermal mineralization which commenced during Upper Carboniferous times is characterized by the following geochemical conditions: (1) low saline Na-K-Mg-Cl fluids with sulfur and oxygen fugacities at the pyrite-pyrrhotite buffer and temperatures of 400-500°C, (2) fluids with CO2, CH4±N2, andpH, Eh, sulfur, and oxygen fugacity in the stability field of graphite + pyrite at temperatures of 280-350° and (3) moderate to high saline Ca-Na-Cl fluids with CH4+ N2; sulfur and oxygen fugacity are in the stability field of pyrrhotite at temperatures <300°C. The latter environment is confirmed by in situ conditions found at the bottom of the deep drilling. Monoclinic, ferrimagnetic pyrrhotite is the main carrier of magnetization which disappears below about 8.6 km, corresponding to in situ temperatures of about 250°C. Below this depth, hexagonal antiferromagnetic pyrrhotite with a Curie temperature of 260°C is the stable phase. Temperature-dependent transformation of pyrrhotite and the reaching of its Curie isotherm within the Earth crust are one of the striking results of the KTB deep drilling project.